Sportmotorische Tests im Kindes- und Jugendalter: Normwertbildung - Auswertungsstrategien - Interpretationsmöglichkeiten ; Überprüfung anhand der Daten des Motorik-Moduls (MoMo) - Oberger, Jennifer (Karlsruher sportwissenschaftliche Beiträge / Institut für Sport und Sportwissenschaft, Karlsruher Institut für Technologie (KIT). Hrsg.: Prof. Dr. Klaus Bös, PD Dr. Michaela Knoll, 2015)
A reliable diagnosis of the state of motor development requires objective and reliable test procedures. As part of the MoMo Baseline Study, the motor fitness of 4529 children and adolescents in Germany was evaluated by using the MoMo Performance Test (11 motor and computer based tests). The data obtained served as a basis for the compilation of nationwide representative standard values. By using these values, it is possible to classify the state of motor fitness and follow its development.